The Effect of Training and Servant Leadership on the Emergence of Work Engagement in Employees of Pt. Bank Sumut Balige Branch During the Covid-19 Pandemic - Sondang A. Y. Nadeak; Onan Marakali Siregar (Journal of Social Research, 2022)
Work engagement with employees is important for the company. The existence of work engagement on employees can improve the company’s performance continuously. To be able to trigger the emergence of work engagement, the company conducts training with the aim of motivating, increasing skills and also expanding knowledge about work. In addition to training, servant leadership is also needed, namely leadership with care and good service, a servant leader makes his subordinates do the same thing as he does. The implementation of training and servant leadership is a challenge for companies considering the current Covid-19 Pandemic. Therefore companies are required to be able to do as much as possible. The study aims to analyze the impact of training and servant leadership on work engagement on employees at PT. Bank Sumut Balige Branch during the covid-19 pandemic. The impact of training and servant leadership will be severely tested, simultaneously against the work engagement. This form of research is a quantitative study with an associative approach. The population in this study is employees of PT. Bank Sumut Balige Branch and Silimbat Sub- Branch Office as many as 32 respondents. The method of analysis used is the validity test, the religious test, the classic assumption test, the linear regression analysis, and the hypothetical test. The result of this research is that Training has no effect and is not significant to the emergence of Work Engagement. Servant Leadership influences the emergence of Work Engagement. Training and Servant Leadership have simultaneous influences. Training and Servant Leadership contributed 24.9% to the emergence of Work Engagement. The rest is influenced by other variables such as organizational culture and other leadership models.